Gerakan Remaja Peduli Kesehatan: Sadari Sebagai Langkah Awal Deteksi Dini Kanker Payudara Pada Siswi Di Sma Madrasah Aliyah Negeri Karawang - Handayani, Dhonal; Basuki, Dita Utari; Shintia, Enok Ulfah; Utami, Erika; Atikah, Euis (Peneliti.net, 2025)
Breast cancer is the type of cancer with the highest prevalence in Indonesia, including in young women. Early detection through Breast Self-Examination (BSE) is an effective preventive measure, but is still not widely implemented among young women due to lack of awareness and information. This activity aims to improve students' knowledge and skills in conducting early detection of breast cancer through BSE education and simulation at SMA Madrasah Aliyah Negeri Karawang. The method used is participatory education through counseling, group discussions, BSE practice simulations, and pre-tests and post-tests to measure changes in knowledge and attitudes. The target of the activity was 40 female students in grade 3 of MAN Karawang. The results of the activity showed a significant increase in students' knowledge, interest, and skills in conducting BSE, with student participation reaching 100% and an increase in knowledge and practice scores after educational intervention. In conclusion, empowerment through BSE education is effective in increasing awareness of young women regarding the importance of early detection of breast cancer, so it is recommended that this education be carried out continuously to build a culture of health awareness from adolescence.